A Look at Grade 2 Writing: Successes and Challenges in Early Literacy Development (LEARNing Landscapes, 2013)
The keys to early literacy development to the end of Grade 2 are a strong foundation in the skills of printing and spelling. These provide the underpinnings that unlock the cognitive and linguistic resources youngsters are developing in the early stages of literacy learning. Illustrative examples of children’s efforts in the writing process at the end of Grade 2 demonstrates the complex interaction between skills, cognitive and metacognitive thought processes, and vocabulary knowledge that launch youngsters into the next steps of literacy—one that significantly challenges them.
Keywords: early childhood; education; literacy; grade 2; cognitive thought process; metacognitive thought process